Optimal reactive power dispatch under unbalanced conditions using hybrid swarm intelligence. (July 2018) - Shareef, SK. Mahammad; Srinivasa Rao, R.
Abstract: This paper focuses on the minimization of the voltage deviation and power loss associated with optimal reactive power dispatch (ORPD) under unbalanced conditions. A combination of two swarming algorithms is proposed called the artificial bee colony with firefly (ABC-FF) algorithm. This algorithm operates on control variables, such as load reactance and voltage and transformer tap settings, which are varied to achieve optimum results. The entire experiment is conducted on two IEEE benchmark test bus systems, namely, the IEEE 14 and the IEEE 39 benchmark bus systems. The experimental results of the proposed ABC-FF approach are compared with those of other evolutionary methods to ensure that the proposed approach provides the best ORPD operation when compared with conventional methods.